PEMBATALAN PERKAWINAN AKIBAT PENYAKIT OBSESSIVE COMPULSIVE DISORDER (OCD) MENURUT MAZHAB SYAFI’I DAN MAZHAB HANAFI - Anshorullah, M.; Purqon, Arip; Saputra, M. Reza Saputra; Saputra, M. Reza (Universitas Islam Negeri Raden Fatah Palembang, 2024)
Marriage is an institution that aims to create a harmonious family life in accordance with sharia principles. However, the presence of certain illnesses, including mental disorders such as Obsessive Compulsive Disorder (OCD), can affect the continuity of a marriage. OCD, which is characterized by recurring obsessions and compulsions, has the potential to disrupt household stability if not disclosed or adequately addressed before or during marriage. This study aims to examine the perspectives of the Shafi'i Mazhab and Hanafi Mazhab regarding the annulment of marriage due to Obsessive Compulsive Disorder (OCD). This study uses a juridical-empirical research method with a qualitative approach through a case study, which focuses on the decision of the Bogor City Religious Court Number 312/Pdt.G/2022/PA.Bgr. The literature used includes fiqh books from leading scholars such as Imam Nawawi, Ibn Qudamah, Imam Abu Hanifah, and Imam Sarakhsi, as well as Indonesian laws and regulations related to marriage annulment. The data was analyzed qualitatively using thematic analysis techniques to identify the main themes and relate them to relevant legal theories and principles. The results of the study show that there are fundamental differences in the approaches of the Syafi'i and Hanafi schools of thought towards marriage annulment due to OCD. The Shafi'i school of thought has stricter criteria, focusing on physical disabilities that are permanent and have a direct impact on sexual life, so that OC is not a cause of marriage annulment. In contrast, the Hanafi school has a more inclusive and flexible approach, taking into account the mental and emotional impact of OCD on a couple's ability to carry out marital duties. The Bogor City Religious Court's decision in this case demonstrates the application of positive law in Indonesia that accommodates mental health considerations as grounds for annulment, in line with the Hanafi school of thought.